2012
DOI: 10.3747/co.19.1003
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Breast Cancer Risk Based on Stem-Cell Theory

Abstract: A Countercurrents Series a with S.A. Narod md• Hormone replacement therapy (hrt) increases breast cancer risk slowly over many years, but the risk disappears within 2 years of cessation 10,11 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…Other research groups have found increased osteogenic differentiation among male ASCs [29, 30], and it is most likely that this in fact represents an increased prevalence of hPSCs. Third, some investigators have noted a reduction in stem cell numbers with the onset of menopause [31]; however, our analysis of pre‐ and postmenopausal liposuction samples did not find any significant association. However, our calculations were based on a mean age of menopause (age 51) rather than a clinical history.…”
Section: Discussioncontrasting
confidence: 86%
“…Other research groups have found increased osteogenic differentiation among male ASCs [29, 30], and it is most likely that this in fact represents an increased prevalence of hPSCs. Third, some investigators have noted a reduction in stem cell numbers with the onset of menopause [31]; however, our analysis of pre‐ and postmenopausal liposuction samples did not find any significant association. However, our calculations were based on a mean age of menopause (age 51) rather than a clinical history.…”
Section: Discussioncontrasting
confidence: 86%
“…Twelve studies reported on costs associated with implementation [ 45 , 48 , 56 , 60 , 61 , 63 , 65 67 , 72 , 74 , 75 ], representing 11 unique programs. Two studies estimated the intervention implementation costs in the set-up year (e.g., purchase of computers and equipment, cleaning, personnel), stating that it cost $US44,821 and $US46,213, respectively [ 45 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study reported the implementation cost to be approximately $350 per participant [ 74 ]. Four studies reported that philanthropic donations were used to support the ongoing organisational costs associated with the exercise intervention [ 61 , 63 , 65 , 75 ]. Hybrid models of funding subsided the costs associated with intervention use, including a mix of fee-for-service (upfront, set cost per session) and subsidised costs (total session costs off-set through donations, sponsorship) [ 48 , 56 , 60 , 63 , 65 , 66 , 72 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the recent past, I have argued in favour of a hypothesis that the relative size of breast stem cell populations may predict cancer risk 9 . If that argument were to be extended to include two different predominant normal stem-cell populations, one of which confers risk for er-positive breast cancers and one of which confers risk for er-negative breast cancers, it might help to explain the similarity between the breasts.…”
Section: A Countercurrents Series a With Sa Narod MDmentioning
confidence: 99%